A Novel Indicator of Myocardial Injury after Acute Myocardial Infarction: 'DPP-3'. (December 2022) - Ozden, Ozge; Yesildas, Cuma; Demir, Mustafa; Surmeli, Ali Orcun; Yesil, Emrah; Orscelik, Ozcan; Celik, Ahmet
Background: Dipeptidyl peptidase 3 (DPP-3) is an intracellular enzyme that causes hemodynamic instability and cardiac depression in several cases such as cardiogenic shock, sepsis and burns where DPP-3 is released into the blood due to cell death. Data on the effect of higher DPP-3 levels on acute coronary syndrome (ACS) patients are currently lacking. The aim of this study was to evaluate the effect of DPP-3 levels on ACS patients. Methods: In this prospective study, we included ACS patients including STEMI and non-STEMI groups and a control group to compare various demographic, echocardiographic and laboratory parameters including DPP-3. DPP-3 levels were measured at 24 th, 48 th, and 72 nd h from the onset of symptoms in ACS patients and then compared with left ventricle ejection fraction (LVEF) for the assessment of left ventricle systolic function. Results: A total of 70 ACS patients (age 62.5 ± 11 years, 68.6% male) were recruited and 48 normal individuals were included as control group (age 61.1 ± 10 years, 66.7% male). It has been demonstrated that DPP-3 levels are significantly higher in the ACS group than the control group like troponin I levels. DPP-3 levels were found to be one of the independent predictors of LVEF similar to NT-proBNP and troponin I. Conclusions: This study suggests that DPP-3 could be an important indicator of myocardial depression predicting left ventricle systolic function in ACS.